Single-dose trastuzumab monotherapy achieved pathological complete response (pCR) in a patient with HER2-positive breast cancer: a case report - Ayaka Isogai; Haruru Kotani; Masataka Sawaki; Masaya Hattori; Akiyo Yoshimura; Ayumi Kataoka; Kazuki Nozawa; Yuri Ozaki; Yuka Endo; Akira Nakakami; Rie Komaki; Hiroji Iwata (Surgical Case Reports)
Abstract Background With advances in breast cancer treatment, the importance of de-escalation therapy to reduce harm during the treatment of elderly patients has attracted attention in recent years. Certain patient populations are expected to have a superior response to anti-HER2 drugs, particularly those with human epidermal growth factor receptor type 2 (HER2)-positive breast cancer. In this report, we describe our experience of dramatic anti-HER2 drug response in a patient who achieved pathological complete response (pCR) with a single dose of trastuzumab. Case presentation An 88-year-old woman presented with a 2-cm palpable mass in the left breast. Vacuum-assisted breast biopsy, ultrasonography, and positron emission tomography–computed tomography revealed estrogen receptor-negative and HER2-positive, T1N0M0, stage I breast cancer. Mastectomy was scheduled within 2 months of the initial visit; however, the patient was anxious about the length of the waiting period and requested medication in the interim. Therefore, prior to surgery, one cycle of trastuzumab monotherapy was administered at the discretion of the attending physician. Postoperative pathology showed no remnant of invasive carcinoma and pCR with only a 0.2-mm ductal carcinoma in situ remnant. The patient refused further medication after surgery because of severe diarrhea after trastuzumab administration. Postoperative treatment was limited to follow-up, and no recurrence was observed at 1 year and 6 months postoperatively. Conclusion This case suggests that trastuzumab monotherapy may be effective in certain patients with HER2-positive breast cancer. In the future, identifying patients who are more likely to respond to trastuzumab, as in this case, will allow for more options regarding de-escalation therapy without chemotherapy, particularly in elderly patients who are concerned about the side effects of chemotherapy.